2010
DOI: 10.1016/j.bbrc.2009.12.095
|View full text |Cite
|
Sign up to set email alerts
|

An epigenetic mechanism for capecitabine resistance in mesothelioma

Abstract: Mesothelioma is an uncommon malignancy whose global incidence continues to rise. The therapeutic standard for advanced disease is intravenous pemetrexed and cisplatin. The antifolate capecitabine is significantly less effective than pemetrexed. The balance between thymidylate synthase (TS), dihydropyrimidine dehydrogenase (DPD), and Thymidine Phosphorylase (TP) is critical to the efficacy of capecitabine. DNA from mesothelioma cell lines was bisulfite treated and examined by MS-PCR, RNA was obtained for real t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 26 publications
1
27
0
Order By: Relevance
“…The antimetabolite drugs such as 5-FU and methotrexate need to be converted further into their most active forms to be therapeutically effective, which does not occur when the target cells lack the enzyme activities (115, 116). For example, in CSCs expression of the thymidine phosphorylase can be inhibited via epigenetically silencing mechanisms such as gene promoter methylation catalyzed by the DNA methyltransferases (DNMTs) , resulting in capecitabine resistance (117). Using inhibitors of DNMTs can thus sensitize the CSCs to capecitabine.…”
Section: Mechanisms Of Csc Chemoresistance - the Multiple Lines Ofmentioning
confidence: 99%
“…The antimetabolite drugs such as 5-FU and methotrexate need to be converted further into their most active forms to be therapeutically effective, which does not occur when the target cells lack the enzyme activities (115, 116). For example, in CSCs expression of the thymidine phosphorylase can be inhibited via epigenetically silencing mechanisms such as gene promoter methylation catalyzed by the DNA methyltransferases (DNMTs) , resulting in capecitabine resistance (117). Using inhibitors of DNMTs can thus sensitize the CSCs to capecitabine.…”
Section: Mechanisms Of Csc Chemoresistance - the Multiple Lines Ofmentioning
confidence: 99%
“…A study by Moghaddam et al found that Tp has angiogenic properties and, in a MCF7 breast cancer xenograft model, Tp overexpression led to faster tumor growth [227]. In contrast, low Tp expression correlates to the favorable prognosis of gastric cancer treated with chemotherapy [228,229] and promoter methylation has been proposed as a mechanism of its expression down regulation in different cancer cells [230,231].…”
Section: Mitochondrial Animal Modelsmentioning
confidence: 99%
“…The 5-Fu cannot be metabolized into an active ingredient in the absence of appropriate intracellular enzymes. Oral capecitabine only works when it is metabolized to 5-Fu by thymidine phosphorylase, however, methylation of this enzyme-encoding gene can lead to drug resistance [50,51].…”
Section: Drug Transportation and Metabolismmentioning
confidence: 99%